Mediators Optimization of Civil Disputes Mediation Process at Post-Perma Court No. 1 of 2016 - Fahri Latukau; Nam Rumkel; Suwarti Suwarti (Journal of Social Science, 2022)
This study aims to analyze the factors causing the unsuccessful mediation process carried out by the mediator in resolving civil disputes, as well as what steps are important for the existence of the mediator in conducting the mediation process for civil disputes in court in accordance with the mandate of Perma Number 1 of 2016. This research method uses empirical legal research, namely research that looks at the application of legislation in society. The research conducted by the researcher belongs to the type of field qualitative research, namely research that emphasizes the completeness of the data collected in the form of primary and secondary data. The results showed that factors that cause the unsuccessful mediation process carried out by the mediator in resolving civil disputes. First,Certified mediator,The first obstacle regulated by the Supreme Court is admitting an intermediary or third party in the mediation process with a certification issued by the Supreme Court. This is an obstacle, why is that? Because basically a third party or mediator in the mediation process is not required to have a mediator certificate. A logical consequence that arises in the courts is also the limited number of judges with the high quality of cases which do not maximize the mediation process. The effectiveness of the implementation of peace efforts is influenced by the number of cases charged to judges. This will actually affect the performance of a judge in seeking peace for the parties. Another obstacle is the facilities and infrastructure in carrying out mediation.